ETHNOMEDICINAL, PHYTOCHEMICAL, AND PHARMACOLOGICAL ASPECTS OF GENUS ACANTHUS - Bora, Rekha; Adhikari, Partha Pradip; Das, Ajit Kumar; Raaman, Nanjian; Sharma, Gauri Dutt (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Acanthus (family Acanthaceae) is a genus of the major group angiosperms (flowering plants) comprising more than 29 species widely distributed in the tropical and subtropical region. The aim of this review is to offer thorough scientific information on ethnomedicinal uses, phytochemical, and pharmacological activities of the plant species belonging to the genus Acanthus. Numerous traditional uses of the genus have been supported in this article from the results, and executed by the extracts and/or pure compounds obtained from pharmacological studies will provide a single platform to help future researches on the genus Acanthus. Furthermore, ethnomedicinal evaluation using fractions or isolation of medicinal principles was extensively explored by databases like Google, Google Scholar, and ScienceDirect at the same time.Â 